EFFECT OF LEADERSHIP, PROFESSIONALISM APPARATUS, INFORMATION TECHNOLOGY AND BUDGETING PROGRAM EFFECTIVENESS OF DIRECTORATE GENERAL OF SMALL AND MEDIUM MINISTRY OF INDUSTRY - Yurisman Star (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
Abstract This study investigates the effect on leadership, Professionalism Apparatus, and availability of Information Technology and Budgeting fairly on Directorate General of Small and Medium Enterprises of the Ministry of Industry in accordance with the need to improve the effectiveness of program development and growth of SMEs. To determine whether these independent variables influencing dependent variables Program Effectiveness either partially or simultaneously. Data collection techniques using questionnaires and literature study, data collected were tabulated and analyzed using Statistical Package for the Social Sciences (SPSS) devices and computer aids. The data analysis focused on the validity, reliability, normality test, multicollinearity, double correlation F test and t test. The Result of research showed that 69% Leadership influences the apparatus professionalism and 75.20% there are significant Information Technology 17.70%, and there are significant budgeting to Program effectiveness of 8.20%. The results of this study are expected to provide an indication that respondents tend to think positively to the statement which is designed in the form of a questionnaire, it shows the programs that are presented for the development and growth of Small and medium enterprise effectively. Keywords: Leadership, Professionalism Apparatus, Information Technology, of the Effectiveness Program Budgeting